Implementing RightsStatements.org at the University of Miami Libraries - Elliot Williams; Laura Capell (Journal of Librarianship and Scholarly Communication, 2018)
INTRODUCTION Library digital collections have historically contained unstandardized and often inadequate information regarding copyright status in the item-level metadata. The development of RightsStatements.org, international recommendations for describing rights status, provides an opportunity for libraries to improve their rights metadata and educate users about copyright for digital objects. DESCRIPTION OF PROGRAM This paper reports on a two-year project at the University of Miami Libraries to implement RightsStatements.org. Two librarians, who did not previously have a background in copyright issues, performed a copyright analysis of all 58,000 objects in the libraries' digital collections and developed workflows for updating rights metadata. Workflows for developing new digital projects were also updated to incorporate rights considerations more comprehensively throughout the process. CONCLUSIONS AND NEXT STEPS The copyright assessment project uncovered several challenges for analyzing the copyright status of digitized archival and special collections materials, including the need to periodically reevaluate materials as more content moves into the public domain in the United States. The project also reinforced the importance of risk management when planning digitization projects for online access. Project outcomes are discussed, as well as implications for other libraries considering implementing RightsStatements.org.